Ru(II)-Chiral (1R,2S)-(+)-cis-1-amino-2-indanol immobilized over SBA-15 for asymmetric transfer hydrogenation reaction of prochiral ketones - Parambadath, Surendran; Singh, A. P. (Catalysis Today, 2009)
Mesoporous SBA-15 (Santa Barbara University at California) has been synthesized and functionalized with (4-chloromethyl)phenyltriethoxysilane, there after the surface silanols groups were passivated by dimethoxydimethylsilane (MeO(2)Me(2)Si) [Bz-SBA-15]. Further (1R,2S)-(+)-cis-1-amino-2-indanol [AIL] has been immobilized over functionalized SBA-15 (BzAIL-SBA-15). The heterogeneous catalysts were synthesized by complexation of BzAIL-SBA-15 by [RuCl(2)(benzene)](2) and [RuCl(2)(p-cymene)](2) in 2-propanol at reflux condition designated as Ru-Bn-BzAIL-SBA-15 (Ru-1) and Ru-Cy-BzAIL-SBA-15 (Ru-2). The synthesized materials have been characterized by small angle X-ray diffraction spectroscopy (SAXS), N(2) adsorption-desorption isotherms, Fourier Transformed-Infra-red (FT-IR) spectroscopy, Transmission Electron Microscopy (TEM), intensively Coupled plasma atomic emission spectroscopy (ICP-AES), Diffuse reflectance UV-vis and (13)C CP MAS NMR analysis. Further the synthesized and characterized materials (Ru-1 and Ru-2) have been successfully applied in the asymmetric transfer hydrogenation (ATH) reaction of simple prochiral ketones, which gave a yield of 56% and 18% and enantiomeric excess (ee) values of 62% and 77% for Ru-1 and Ru-2, respectively, after 1 h for acetophenone. The reusability studies showed approximately the same enantiomeric excess value at lower conversions. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric transfer hydrogenation; Chiral amino alcohols; Mesoporous molecular sieve; Prochiral ketones; SBA-15

Ru(II)-functionalized SBA-15 as highly chemoselective, acid free and sustainable heterogeneous catalyst for acetalization of aldehydes and ketones - Lazar, Anish; Betsy, K. J.; Vinod, C. P.; Singh, A. P. (Catalysis Communications, 2018)
Combining electron deficient Ru(II) coordination sites with organofunctionalized SBA-15, (L)Ru(Il)@SBA-15, result in a mild, neutral, water scavenger free and chemo-selective acetalization catalyst for cyclic/acyclic acetals. Vacant coordination sites of ruthenium in (L)Ru(II)@SBA-15 activates protecting groups as well as reactants simultaneously and restricts the reverse acetalization reaction. Synthesized (L)Ru(Il)@SBA-15 catalyst has been thoroughly characterized and act as competitive catalyst compared to conventional acid catalysts. (L) RuaD@SBA-15 performs high catalytic activity as well as selectivity within 20 min with high TOF. The catalyst can be recycled and reaction parameters are optimized.
Keywords: Acetalization reactions; Acid free; chemo-selective; heterogeneous catalyst; Reusable; Ru(II) immobilized SBA-15